2020
DOI: 10.1186/s13046-020-01603-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of CRISPR/Cas9 development and its prospect in hepatocellular carcinoma treatment

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies today. Patients suffer from HCC since its high malignancy and limited treatment means. With the development of genetic research, new therapeutic strategy comes up in the way of gene editing. Clustered regularly interspaced short palindromic repeat/CRISPRassociated nuclease 9 (CRISPR/Cas9) was discovered as an immune sequence in bacteria and archaea. After artificial transformation and follow-up research, it is widely used as a gene editing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“… 94 CRISPR-Cas9 has also shown great potential in the treatment of cancer, including HCC. 95 , 96 Wang et al reported that the knockout of CXC chemokine receptor 4 (CXCR4), associated with a poor prognosis in HCC, by CRISPR/Cas9 not only suppresses proliferation and invasion but also increases sensitivity to the anticancer drug cisplatin in HCC. 97 Another study has shown that the CRISPR/Cas9-mediated knockout of nuclear receptor binding SET domain-containing protein 1 inhibits the ability of HCC cells to proliferate and migrate.…”
Section: Overview Of Hcc Therapy Targeting Bmi1mentioning
confidence: 99%
“… 94 CRISPR-Cas9 has also shown great potential in the treatment of cancer, including HCC. 95 , 96 Wang et al reported that the knockout of CXC chemokine receptor 4 (CXCR4), associated with a poor prognosis in HCC, by CRISPR/Cas9 not only suppresses proliferation and invasion but also increases sensitivity to the anticancer drug cisplatin in HCC. 97 Another study has shown that the CRISPR/Cas9-mediated knockout of nuclear receptor binding SET domain-containing protein 1 inhibits the ability of HCC cells to proliferate and migrate.…”
Section: Overview Of Hcc Therapy Targeting Bmi1mentioning
confidence: 99%
“…Cas9, a multifunctional protein, possesses two nuclease structural domains, HNH and RuvC. The HNH domain cuts the DNA strand complementarily paired with crRNA, and the RuvC domain cuts the other strand of double-stranded DNA (Stovicek et al 2017 ; Wu et al 2020 ). Cas9 becomes a single-stranded cleaved protein if one of the two structural domains is mutated, and if both are mutated, Cas9 becomes a protein with only DNA-binding activity (Young et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cas9, a multifunctional protein, possesses two nuclease structural domains, HNH and RuvC. The HNH domain cuts the DNA strand complementarily paired with crRNA, and the RuvC domain cuts the other strand of double-stranded DNA (Stovicek et al, 2017;Wu et al, 2020). Cas9 becomes a single-stranded cleaved protein if one of the two structural domains is mutated, and if both are mutated, Cas9 becomes a protein with only NDAbinding activity (Young et al, 2019).…”
Section: Introductionmentioning
confidence: 99%